Poets of the Bible : from Solomon's Song of songs to John's Revelation - Barnstone, Willis, 1927-; Barnstone, Willis, 1927- (W.W. Norton, 2017)
"The world's greatest poetry resides in the Bible, yet these major poets are traditionally rendered into prose. In this pioneering volume of biblical poets translated in English, Willis Barnstone restores the lyricism and power of the poets' voices in both the New and Old Testaments. In the Hebrew Bible we hear Solomon rhapsodize in Song of Songs, David chant in Psalms, God and Job debate in grand rhetoric, and prophet poet Isaiah plead for peace. Jesus speaks in wisdom verse in the Gospel, Paul is a philosopher of love, and John of Patmos roars majestically in Revelation, the Bible's epic poem. This groundbreaking volume includes every major biblical poem from Genesis and Adam and Eve in the Garden to the last pages of Alpha and Omega in Paradise."--Dust jacket.